Monetary policy in Brazil: evidence from new measures of monetary shocks - Adonias Evaristo da Costa Filho (Universidade de São Paulo, 2017)
This paper derives new measures of monetary policy shocks for Brazil. First, one set of shocks is built inspired on the Romer and Romer (2004) methodology, using official and private forecasts. Central Bank staff forecasts were collected from the technical presentations of monetary policy meetings, released after the introduction of the Access of Information Law, while private forecasts come from the Focus survey. Second, a yield curve factor shock is constructed for the Brazilian case, based on the Barakchian and Crowe (2013) methodology. Equipped with the shocks measures, we feed them on VARs (Vector Autoregressions) and analyze the effects on inflation and output. A standardized monetary policy shock is found to reduce real GDP in up to 0.5%. In all but the yield curve shock case, it is found evidence of a price puzzle in the estimated models.